Answers

2014-10-03T19:09:16+05:30
(x-5)(x-6) = 25/567
⇒  x²-6x-5x+30 = 5/24
x²-10x+25-(x-5) = 5/24 
⇒  (x-5)²-(x-5)-(5/24)² = 0
⇒   y²-y-(5/24)² = 0
⇒   y²-25y/24+y/24-5²/24² = 0
⇒      y(y-25/24) 1/24(y-25/24) = 0
⇒      (y-25/24)(y+1/24) = 0
⇒     y-25/24 = 0 ,   then  y = 25/24
therefore,    x-5 = 25/24 ,⇒  x = 25/24+5 = 145/24
    And  y+1/24 = 0,   then y = -1/24
therefore,   x-5 = -1/24 ,  ⇒   x = 5-1/24 = 119/24
the values of x are 145/24 and 119/24
1 5 1
try to put your answers in the equations. It won't satisfy the equation.
ok i try
correct answers are 119/24,145/24
oh yes i mis calculated
thank you
The Brainliest Answer!
2014-10-03T19:42:59+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Take (x-6) = t
 then (x-5) = (t+1)

(x-5)+(x-6) = 25/576
⇒(t+1)t = 25/576

⇒t² + t -  \frac{25}{576} = 0

t =  \frac{-1+ \sqrt{1^2-4*1*(-25/576)} }{2*1} and  \frac{-1+ \sqrt{1^2-4*1*(-25/576)} }{2*1}

or t =  \frac{1}{24} and  \frac{-25}{24}

But t = (x-6)
case: 1 
t = 1/24
⇒x-6 = 1/24
⇒x = 6 + 1/24
⇒x = (144+1)/24
x = 145/24
case: 2
t = -25/24
⇒x-6 = -25/24
⇒x = 6 -25/24
⇒x = (144-25)/24
x = 119/24


1 5 1